Structural analysis of the bright monomeric yellow‐green fluorescent protein mNeonGreen obtained by directed evolution. Issue 12 (5th December 2016) - Clavel, Damien; Gotthard, Guillaume; von Stetten, David; De Sanctis, Daniele; Pasquier, Hélène; Lambert, Gerard G.; Shaner, Nathan C.; Royant, Antoine
Abstract : The structures of the fluorescent proteins lan YFP and mNeonGreen from B. lanceolatum are described, providing a structural understanding of the directed evolution process from lan YFP to mNeonGreen. A specific radiation‐damage study has been performed for mNeonGreen. Abstract : Until recently, genes coding for homologues of the autofluorescent protein GFP had only been identified in marine organisms from the phyla Cnidaria and Arthropoda. New fluorescent‐protein genes have now been found in the phylum Chordata, coding for particularly bright oligomeric fluorescent proteins such as the tetrameric yellow fluorescent protein lan YFP from Branchiostoma lanceolatum . A successful monomerization attempt led to the development of the bright yellow‐green fluorescent protein mNeonGreen. The structures of lan YFP and mNeonGreen have been determined and compared in order to rationalize the directed evolution process leading from a bright, tetrameric to a still bright, monomeric fluorescent protein. An unusual discolouration of crystals of mNeonGreen was observed after X‐ray data collection, which was investigated using a combination of X‐ray crystallography and UV–visible absorption and Raman spectroscopies, revealing the effects of specific radiation damage in the chromophore cavity. It is shown that X‐rays rapidly lead to the protonation of the phenolate O atom of the chromophore and to the loss of its planarity at the methylene bridge.